EXTRACTS OF SALVIA MILTIORRHIZA BUNGE ON THE CYTOKINES OF RAT ENDOMETRIOSIS MODELS - Zhou, Zan-Hua; Weng, Qing; Zhou, Jian-Hong; Zhou, Jue (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Endometriosis is a common mysterious and fascinating gynaecological condition with diverse clinical manifestations, highly variable and unpredictable clinical course with decreased quality of life. Clinically, Salvia miltiorrhiza Bunge (SMB, Chinese Danshen) has been applied to treat endometriosis and get satisfactory results. The present study was aimed to explore the effects of the extracts of SMB (ESMB) on the serum levels of cancer antigen 125 (CA-125) and the levels of interleukin (IL)-13, IL-18 and tumor necrosis factor-alpha (TNF-alpha) in the peritoneal fluids of rat endometriosis models. Three extraction methods for SMB were compared, which are the sample extracted with conventional method, the sample extracted with espresso coffee machine and the commercial condensed powder of natural products. We determined tanshinone IIA, salvianolic acid B and danshensu in the ESMB of different extraction methods. Forty female Sprague-Dawley (SD) rats were randomly divided into ESMB group, Danazol (positive control) group, model group and the sham-operation group (Sham group). After all the treatment ended, the serum levels of CA125 and the levels of IL-13, IL-18 and TNF-alpha in the peritoneal fluids of rat endometriosis models were measured using enzyme-linked immune-sorbent assay (ELISA) as directed by the manufacturer. The extraction efficiency of the ESMB samples extracted with coffee machine ranged from 600μm to 710μm was the highest. The serum levels of CA-125 and the levels of IL-18 and TNF-alpha in the peritoneal fluids of ESMB group, Danazol group and Sham group were significantly lower than those of the Model group (P<0.05). The serum levels of CA-125 and the levels of IL-18 and TNF-alpha in the peritoneal fluids of Danazol group and ESMB group were significantly higher than those of Sham group, respectively (P<0.05), and no marked difference existed between them (P>0.05). The levels of IL-13 in the peritoneal fluids of ESMB group, Danazol group and Sham group were significantly higher than those of the Model group (P<0.05). The levels of IL-13 in the peritoneal fluids of ESMB group and Danazol group were significantly lower than those of Sham group (P<0.05), and there was no marked difference between ESMB group and Sham group (P>0.05). ESMB shows promises in treating endometriosis by markedly decreasing the serum levels of CA-125 and the levels of IL-18 and TNF-alpha in the peritoneal fluids and significantly increasing the levels of IL-13 in the peritoneal fluids.